An Update of Dental Implantology and Biomaterial 2019
DOI: 10.5772/intechopen.80965
|View full text |Cite
|
Sign up to set email alerts
|

Abutment Selection for Anterior Implant-Supported Restorations

Abstract: With the introduction of dental implants to the market, varying restorative options have been successfully added for restoring the function and esthetics of both completely and partially edentulous patients. Accurate prosthodontic rehabilitation is the key factor for providing the long-term success and the survival of osseointegrated implants. Implantsupported restorations can be fabricated with different techniques. The prefabricated abutments provided by the implant companies are accepted as the gold standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…A zirconia framework is made up over a titanium neck. This system is called a "hybrid zirconia abutment" or "ti-base abutment" [19].…”
mentioning
confidence: 99%
“…A zirconia framework is made up over a titanium neck. This system is called a "hybrid zirconia abutment" or "ti-base abutment" [19].…”
mentioning
confidence: 99%
“…Although, the number of each abutment groups were not equal and too small. Labial bone thickness and height showed a tendency to decrease in some abutments from 0-2 years to 5 years (table 12,13). Similar to previous studies, Degidi and colleagues (30) also reported 29% and 26% of initial bone width and height was resorbed horizontally and vertically after 1 year recall of immediate implant placement.…”
Section: Labial Bone Thickness (Mean±sd Mm) 0-2 Years Average 5 Years...supporting
confidence: 80%
“…Titanium has been used as implant abutment for decades due to its strength and biocompatibility to soft tissue. It is considered as a gold standard abutment because of high success rate and its properties (12,13). However, titanium abutment in anterior region possibly showed greyish color of soft tissue around implant and effect to esthetic outcome (14).…”
Section: Implant Abutment Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, dental implants have been the treatment of choice for replacing a single missing tooth, especially in the aesthetic zone, owing to its high clinical success [ 1 – 3 ]. Historically, there have been several different types of dental implant abutments used in the aesthetic zone, such as metal-colored implant abutments, tooth-colored implant abutments, and two-piece or hybrid abutments [ 4 ]. Regarding the material, titanium is commonly used as a dental implant abutment [ 1 ].…”
Section: Introductionmentioning
confidence: 99%